BIOMIMETIC RESTORATIVE DENTISTRY: INTEGRATED LABORATORY AND CLINICAL ASSESSMENT OF STRENGTH, MARGINAL ADAPTATION, PULP VITALITY AND RESTORATION SURVIVAL - Shakhnоza K. Musashaykhova; Gulrukh B. Ishniyazova (Modern American Journals, 2025)
Objective. To provide a holistic evaluation of biomimetic restorative approaches versus conventional methods in terms of mechanical strength, marginal seal, maintenance of pulp vitality, and 12‑month clinical survival.
Keywords: Biomimetic restoration; composite materials; microleakage; pulp vitality; fatigue resistance; restoration survival.